PENGARUH BACK MASSAGE TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI: LITERATURE REVIEW - Fitri Yulita, Rita (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
According to the World Health Organization (2019) hypertension is the cause of premature death throughout the world. Increased blood pressure that lasts for a long time (persistent) can cause a damage to kidneys (renal failure), heart (coronary heart disease), and brain (stroke). One of the efforts to prevent this is by performing back massage therapy, which can vasodilate blood vessels and increase the reflex baroreceptor response so that it affects the decrease in sympathetic nervous system activity and increases the activity of the parasympathetic nervous system. The purpose of this literature review is to identify the effect of back massage on blood pressure in hypertensive patients. This research method uses a literature review with a systematic literature review approach. This research was conducted using online search methods through several search engines including Google Scholar, Garuda, Science Direct, EBSCO, and PubMed using the keywords